Ventrolateral origin of each cycle of rhythmic activity generated by the spinal cord of the chick embryo. - Yoshiyasu Arai; George Z Mentis; Jiang-Young Wu; Michael J O'Donovan (PLoS ONE)
Background The mechanisms responsible for generating rhythmic motor activity in the developing spinal cord of the chick embryo are poorly understood. Here we investigate whether the activity of motoneurons occurs before other neuronal populations at the beginning of each cycle of rhythmic discharge. Methodology/principal findings The spatiotemporal organization of neural activity in transverse slices of the lumbosacral cord of the chick embryo (E8-E11) was investigated using intrinsic and voltage-sensitive dye (VSD) imaging. VSD signals accompanying episodes of activity comprised a rhythmic decrease in light transmission that corresponded to each cycle of electrical activity recorded from the ipsilateral ventral root. The rhythmic signals were widely synchronized across the cord face, and the largest signal amplitude was in the ventrolateral region where motoneurons are located. In unstained slices we recorded two classes of intrinsic signal. In the first, an episode of rhythmic activity was accompanied by a slow decrease in light transmission that peaked in the dorsal horn and decayed dorsoventrally. Superimposed on this signal was a much smaller rhythmic increase in transmission that was coincident with each cycle of discharge and whose amplitude and spatial distribution was similar to that of the VSD signals. At the onset of a spontaneously occurring episode and each subsequent cycle, both the intrinsic and VSD signals originated within the lateral motor column and spread medially and then dorsally. By contrast, following a dorsal root stimulus, the optical signals originated within the dorsal horn and traveled ventrally to reach the lateral motor column. Conclusions/significance These findings suggest that motoneuron activity contributes to the initiation of each cycle of rhythmic activity, and that motoneuron and/or R-interneuron synapses are a plausible site for the activity-dependent synaptic depression that modeling studies have identified as a critical mechanism for cycling within an episode.